Spatiotemporal patterns of fish community composition in Great Lakes drowned river mouths. Issue 4 (27th June 2014) - Janetski, David J.; Ruetz, Carl R.
Abstract Freshwater river mouths in large lakes are centres of biological activity, yet little is understood about the spatial and temporal dynamics of fish communities in these systems. In the Laurentian Great Lakes, we sampled littoral fishes over 3 years in six drowned (i.e., protected) river mouths to: (i) quantify spatial (among river mouths) and temporal (among years) variation, (ii) evaluate associations with environmental conditions and (iii) assess spatial patterns of community similarity. We sampled 6787 fish representing 43 species over the course of the study. Multivariate analyses indicated that variation in fish species composition was more strongly partitioned among river mouths than among years. Fish communities across the six river mouths were partitioned into three groups, a pattern we attribute to variability in anthropogenic disturbance and environmental conditions. Canonical correspondence analysis showed that fish species composition was associated with specific conductivity, vegetation cover, turbidity and pH, suggesting species–environment relationships are similar to those shown for Great Lakes coastal wetlands. Finally, we found a negative relationship between geographic distance and community similarity, suggesting that dispersal and/or environmental gradients play a role in shaping these river mouth fish assemblages. We conclude that Great Lakes drowned river mouths can harbour diverse and spatially variable fish assemblages that are driven by a combination of local and regional factors.